Graph-based representations in pattern recognition : 11th IAPR-TC-15 International Workshop, GbRPR 2017, Anacapri, Italy, May 16-18, 2017, Proceedings /: 11th IAPR-TC-15 International Workshop, GbRPR 2017, Anacapri, Italy, May 16-18, 2017, Proceedings. (2017) - Unknown
No abstract available